2014
DOI: 10.1371/journal.pone.0099271
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline, Dopamine D2 Receptor Agonist, Prevents Neuronal Cell Death under Oxidative Stress via Reducing Excitotoxicity

Abstract: Several lines of evidence demonstrate that oxidative stress is involved in the pathogenesis of neurodegenerative diseases, including Parkinson's disease. Potent antioxidants may therefore be effective in the treatment of such diseases. Cabergoline, a dopamine D2 receptor agonist and antiparkinson drug, has been studied using several cell types including mesencephalic neurons, and is recognized as a potent radical scavenger. Here, we examined whether cabergoline exerts neuroprotective effects against oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(80 reference statements)
0
16
0
2
Order By: Relevance
“…Sulpiride also abolished the protection of dopaminergic neurons by ropinirole against 6-OHDA [9]. In SHSY-5Y cells expressing D 2 receptors the protective effect of cabergoline against paraquat toxicity was partially reduced by inhibition of the D 2 receptor with clozapine [1], and recently it was shown that in cortical neurons cabergoline prevented cell death induced by H 2 O 2 through a D 2 receptor-mediated mechanism [18]. In contrast, the protection of THir neurons against rotenone toxicity by cabergoline appears independent of dopamine receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulpiride also abolished the protection of dopaminergic neurons by ropinirole against 6-OHDA [9]. In SHSY-5Y cells expressing D 2 receptors the protective effect of cabergoline against paraquat toxicity was partially reduced by inhibition of the D 2 receptor with clozapine [1], and recently it was shown that in cortical neurons cabergoline prevented cell death induced by H 2 O 2 through a D 2 receptor-mediated mechanism [18]. In contrast, the protection of THir neurons against rotenone toxicity by cabergoline appears independent of dopamine receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshioka et al reported that cabergoline normalized the dopamine turnover in the striatum of 6-OHDA-treated mice [32]. Finally, in cultures of cortical neurons cabergoline prevented H 2 O 2 -induced neuronal cell death by reducing excitotoxicity [18].…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, it is also activated in some neuronal cells under H 2 O 2 induced oxidative stress [47]. The effect of ERK1/ 2 activation on the pro-survival or pro-apoptotic roles in the cells depends on the kinetics, duration, stimulus and cell type [42,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In primary cortical cells, H 2 O 2 was reported to have activated both ERK1/ 2 and p-38 MAP kinase signaling protein in a concentration and time dependent manner [49]. Studies on plant bioactives such as kukoamine B and loganin in human neuroblastoma ShSy5y cells, have been reported to provide neuroprotection against H 2 O 2 induced oxidative stress via attenuation of phospho-ERK1/2 [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Monoamine oxidase B (MAO-B) inhibitors can prevent neuronal loss by inducing neuroprotective genes, anti-oxidant enzymes, and redox proteins [45]. In addition, some dopamine D2/D3 receptor agonists block neuronal cell death under oxidative stress [46], and protect against glutamate toxicity via inactivation of pro-apoptotic factors [47] and up-regulation of glutamate transporters [48]. Moreover, dopamine plays an important role in neuroplasticity [4951], and activation of D1/D5 receptors can prevent the internalization of AMPA and NMDA receptors caused by oligomeric amyloid- beta (Aβ) peptides [52], suggesting that increased DA transmission may protect against Aβ-mediated impairments in synaptic plasticity and their neurotoxic repercussions [5355].…”
Section: Discussionmentioning
confidence: 99%